Ultrasound-guided sclerotherapy for benign non-thyroid cystic mass in the neck - Ji-hoon Kim (Ultrasonography, 2014)
Surgical excision has traditionally been the treatment of choice for benign non-thyroid cystic neck masses, including lymphatic malformation, ranula, branchial cleft cyst, thyroglossal duct cyst, and parathyroid cyst. However, there is a tendency toward recurrence after surgery, and surgery may be accompanied by complications, including nerve injuries, vascular injuries, and scar formation. Ultrasound-guided sclerotherapy using various agents has been challenged and successfully applied as an alternative treatment for benign non-thyroid cystic neck masses. This report reviews the available sclerosing agents and describes the applications of sclerotherapy to the treatment of benign cystic masses in the neck.